Neuropsychiatric Manifestations, Reduced Self-Esteem and Poor Quality of Life in Children and Adolescents with Neurofibromatosis Type 1 (NF1): The Impact of Symptom Visibility and Bullying Behavior - Nicola Davide Cavallo; Gianpaolo Maggi; Francesco Ferraiuolo; Anna Sorrentino; Silverio Perrotta; Marco Carotenuto; Gabriella Santangelo; Claudia Santoro (MDPI AG, 2023)
Neurofibromatosis type 1 (NF1) is an autosomal dominant condition, associated with neurocutaneous manifestations and neuropsychiatric manifestations. The present study explored the prevalence of bullying/cyberbullying behaviors and victimization behaviors in a cohort of children and adolescents with NF1. Possible gender differences and predictors of psychological symptoms, quality of life (QoL), and self-esteem were also examined. Thirty-eight school-aged participants with NF1 completed a psychological evaluation designed to assess anxiety and depression symptomatology, QoL, self-esteem, and the prevalence and extent of bullying/cyberbullying and victimization behaviors. We found that our participants frequently reported victimization behaviors rather than bullying/cyberbullying ones. Moreover, participants complained of depressive and anxiety symptomatology together with reduced self-esteem, and low psychosocial quality of life, with females reporting more severe performances than males. Furthermore, we found that reduced self-esteem was associated with more visibility of the NF1 symptoms, and victimization behaviors were found to mediate the relationship between anxiety and psychosocial QoL. Our findings indicated the presence of a maladaptive loop in children and adolescents with NF1 patients characterized by psychological symptoms, unfavorable self-perception, low self-esteem, and psychosocial difficulties that might be worsened by experiencing victimization behaviors. These results suggest the need to use a multidisciplinary approach in the diagnosis and treatment of NF1.